What Changed after “Peril and Promise”? An Analysis of Higher Education in Developing Countries - Varghese, N.V. (International Journal of African Higher Education, 2016)
“Peril and Promise” (Task Force, 2000) was published when higher education in developing countries was under great stress and strain. The sector received only peripheral reference in development discourses, no priority in resource allocations, and low returns on investments. The higher education sector in developing countries was growing slow and gross enrollment ratios (GERs) were low. This article attempts to analyze the transformation of the sector in the period after “Peril and Promise:” its revival; new forms of globalization; the move away from government funding and control and the ascent of private providers; the sector’s successful survival of severe global economic crises; and new forms of government and management. — « Péril et promesse » (Groupe de Travail sur l’Enseignement Supérieur et la Société, 2000) fut publié alors que l’enseignement supérieur subissait une importante pression et était mis en difficulté. Le secteur n’était mentionné qu’en annexe dans les discours sur le développement, ne bénéficiait d’aucune priorité dans les attributions de ressources et ne recevait que de faibles retours sur investissements. La croissance du secteur de l’enseignement supérieur dans les pays en voie de développement était lente et le taux brut de scolarisation (TBS) bas. Cet article cherche à analyser la transformation du secteur durant la période qui a suivi la publication de “Péril et promesse” : son renouveau, les nouvelles formes de mondialisation, la réduction des financements gouvernementaux et du contrôle gouvernemental couplé à l’ascension des prestataires privés, la survie remarquable du secteur face à de sévères crises économiques mondiales, et l’apparition de nouvelles formes de gouvernement et de gestion.